The contribution of Uzbekistan to the victory over fascism Text - H.Yuldashev translators (Tashkent PPCH Uzbekistan, 2020)
We express our gratitude to the ministries and orgnizations,museums and archives,vaterans andtheir families,scientists and specialists of this field for the collaboration in the preparation of this book.